Técnicas de geoprocessamento aplicadas à identificação e avaliação de nascentes como contribuição à preservação ambiental: margem esquerda do rio Guassupi – São Martinho da Serra – RS - Sangoi, Matheus Bolzan (2024)
On the left bank of the Guassupi River, in the municipalities of São Martinho da Serra and Júlio de Castilhos, within the Plateau of Araucarias, a considerable presence of closed depressions with circular forms and drainage heads of various shapes, such as elliptical, irregular-elliptical, bulbiform, linear, and branched, is observed. This research aimed to apply geoprocessing techniques as an effective tool for identifying and classifying closed depressions and drainage heads, recognizing them as springs and water sources, emphasizing the urgency of conserving these areas. The methodology included the analysis of these features based on variables such as hypsometry, slope, Multiple Flow Direction, morphostructural lineaments, circularity index, land use and land cover classification, and the kernel density estimation map providing essential data and information for the location and characterization of these areas. The land use and land cover map, especially the areas designated for preservation, were decisive in highlighting the reality of the environmental-agricultural conflict, identifying that the springs are unprotected under the law, particularly in areas classified as temporary crops dedicated to soybean cultivation. Fieldwork was crucial and allowed for confirmation, validating the information studied. The adopted methodology represented a significant advancement in the research, enabling the identification of springs in the study area without the initial need for on-site visits, except for confirmation purposes. The results reinforce that these features are indeed springs and water sources, emphasizing the need for proper and balanced management of agricultural practices while respecting the necessary limits for preserving local biodiversity. Ultimately, this dissertation not only provided valuable information but also offered tools that can enhance the precision of work for managers, responsible authorities, and future researchers dedicated to the preservation of these areas.